The manifold role of octapeptide repeats in prion protein assembly. Issue 2 (30th January 2023) - Guadagno, Amy H.; Medina, Scott H.
Abstract: Prion protein misfolding is associated with fatal neurodegenerative disorders such as kuru, Creutzfeldt–Jakob disease, and several animal encephalopathies. While the C‐terminal 106–126 peptide has been well studied for its role in prion replication and toxicity, the octapeptide repeat (OPR) sequence found within the N‐terminal domain has been relatively under explored. Recent findings that the OPR has both local and long‐range effects on prion protein folding and assembly, as well as its ability to bind and regulate transition metal homeostasis, highlights the important role this understudied region may have in prion pathologies. This review attempts to collate this knowledge to advance a deeper understanding on the varied physiologic and pathologic roles the prion OPR plays, and connect these findings to potential therapeutic modalities focused on OPR‐metal binding. Continued study of the OPR will not only elucidate a more complete mechanistic model of prion pathology, but may enhance knowledge on other neurodegenerative processes underlying Alzheimer's, Parkinson's, and Huntington's diseases. Abstract :